Random fixed points and approximations in random convex metric spaces. (1993) - Beg Beg, Ismat Ismat; Shahzad Shahzad, Naseer Naseer
Abstract : Some random fixed point theorems in random convex metric spaces are obtained. Results regarding random best approximation on random convex metric spaces are also proved.